If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 5b = -2(1 + -8b) 9 + 5b = (1 * -2 + -8b * -2) 9 + 5b = (-2 + 16b) Solving 9 + 5b = -2 + 16b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-16b' to each side of the equation. 9 + 5b + -16b = -2 + 16b + -16b Combine like terms: 5b + -16b = -11b 9 + -11b = -2 + 16b + -16b Combine like terms: 16b + -16b = 0 9 + -11b = -2 + 0 9 + -11b = -2 Add '-9' to each side of the equation. 9 + -9 + -11b = -2 + -9 Combine like terms: 9 + -9 = 0 0 + -11b = -2 + -9 -11b = -2 + -9 Combine like terms: -2 + -9 = -11 -11b = -11 Divide each side by '-11'. b = 1 Simplifying b = 1
| 2w+3-5w=9 | | 4x+3+6x=73 | | -3/4-3/8m | | 4(3*2x)=3(2x+4x) | | 9(2x+6)+2x=134 | | 4s^2-144= | | X-7=3z | | 9(2x+6)+2x= | | C=x^2+5x+65 | | 0=x^2+50x+500 | | 6(5k-8)-20=11(2k-3)-3 | | 25x+17=2 | | 9+5b=-2(-8b) | | 10/4=15/x | | F(-3)=2x^2-7x+1 | | 3(y-2)-2(5y-1)=10 | | 2n-n=6*4 | | 3x^2-x-10=46 | | 6x+8+x=71 | | (2-3y)5+(8-y)*(-4)=0 | | 18-6c=-6 | | 7x+12=4x-6 | | -6xt-7=17 | | 41=4x+x+1 | | h^3=4 | | n-20=72 | | 7x+12=4x+50 | | -5t+8+5t-8= | | 1=4.5-1.33p | | 3.3/2 | | 3b^2-25b+63=0 | | 3.3/3 |